Research progress on mitochondria in bone defect repair: mechanisms and therapeutic implications - Hu, Zhicheng; Chen, Gang; Long, Zhisheng (Frontiers in Bioengineering and Biotechnology, 2026)
Bone defect repair faces clinical challenges due to complex conditions caused by various factors such as trauma and aging. Traditional treatments have certain limitations, which seriously affect patients’ prognosis. As the core organelle of cells, mitochondria regulate the activity of key cells including osteoblasts, osteoclasts, and bone marrow mesenchymal stem cells through functions such as oxidative phosphorylation (OXPHOS), production and scavenging of reactive oxygen species (ROS), regulation of Ca2+ concentration, modulation of cell death, and immune response, as well as dynamic processes including fusion, fission, mitophagy, and transport. Moreover, mitochondria interact synergistically with the neuro-vascular-muscle axis, participating deeply in bone defect repair. This article systematically reviews the mechanisms and research progress of mitochondria in bone defect repair, providing a theoretical basis for the development of novel mitochondria-targeted repair strategies and facilitating the research and development of efficient clinical treatment regimens. This will help to develop new treatment strategies for bone defects. These strategies will be more effective, safe and targeted for individual patients.